2020
DOI: 10.1101/2020.10.19.346213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell analysis of cell fate bifurcation in the chordateCiona

Abstract: Inductive signaling interactions between different cell types are a major mechanism for the further diversification of embryonic cell fates. Most blastomeres in the model chordate Ciona robusta become restricted to a single predominant fate between the 64-cell and mid-gastrula stages. We used single-cell RNAseq spanning this period to identify 53 distinct cell states, 25 of which are dependent on a MAPK-mediated signal critical to early Ciona patterning. Divergent gene expression between newly bifurcated sibli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 99 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Vegetal FGF signaling was shown to regulate Foxa.a expression in the notochord, which directly activates Brachyury expression (Reeves et al, 2021). Single‐cell RNA sequencing of Ciona embryos treated with the MAPK inhibitor U0126 showed that most FGF‐dependent cell bifurcations were translated to the sibling cell type revealing that most cell fate decisions were dependent on MAPK signaling through the Ets family transcription factor Elk1/3/4 (Winkley et al, 2021).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Vegetal FGF signaling was shown to regulate Foxa.a expression in the notochord, which directly activates Brachyury expression (Reeves et al, 2021). Single‐cell RNA sequencing of Ciona embryos treated with the MAPK inhibitor U0126 showed that most FGF‐dependent cell bifurcations were translated to the sibling cell type revealing that most cell fate decisions were dependent on MAPK signaling through the Ets family transcription factor Elk1/3/4 (Winkley et al, 2021).…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…We electroporated this library into fertilized Ciona eggs. We collected embryos at the late gastrula stage when notochord cells are developing (Jiang and Smith, 2007) and both Zic and ETS are expressed (Imai et al, 2004; Winkley et al, 2021) (5.5 hours post fertilization, hpf). At this timepoint, we isolated mRNA and DNA.…”
Section: Resultsmentioning
confidence: 99%